Dental care for patients with special needs at a private higher education institute: Dentistry and special patients - Franco Ricardo, Ana Lucia; Arai Yoshida, Rosemeire; Guaré, Renata Oliveira; Cardoso, Cristiane de Almeida Baldini; Lopes, Sérgio Lúcio de Castro; Fardim, Karolina; Costa, André Luiz Ferreira; Botti Rodrigues dos Santos, Maria Teresa (Brazilian Dental Science, 2023)
Objective: Patients with special needs are those individuals who need special care for an undetermined period of time or for lifetime. The present study is aimed to address the dental care of special needs patients at a private higher education institute in the city of São Paulo. Material and Methods: A descriptive, retrospective study was performed for analysis of 210 dental records of special needs patients who were treated at the Dental Department for Special Patients of the Cruzeiro do Sul University between 2012 and 2018. Data on gender, age, diagnosis of the debilitating condition, reason of the consultation, continued use of medications, radiographic images and dental treatments provided were all collected before being submitted to descriptive and inferential statistical analysis (chi-square test) at a significance level of 5%. Results: As for the types of dental procedures assessed in the present study, of the 210 patients, 24% needed dental curative treatments in which periodontal therapy was the most prevalent type, whereas endodontic treatments had the lowest prevalence, representing 4% only. There was a high prevalence of chronic systemic diseases, affecting 56% of the dental records, whose age group was above 40 years old. Conclusion: Regular dental check-ups should be prioritized in patients with special needs to avoid more invasive interventions as found in our group. KEYWORDS Dental care for disabled patients, disabled person; Health profile; Oral treatment; Special needs.